User-Centred Design Approach in Designing Motorcycle Tire Dismounting Tool for One-Handed User - Sudin, Mohd Nizam (2013)
User-Centred Design (UCD) is an approach which aims to improve the management of user requirements in the product development process. The main aim of this approach is to incorporate the users into the product development process in very early phase, as to obtain direct requirements and immediate feedback from them. This paper presents the integration of prescriptive model of product development process and UCD within a practical environment. The integrated process was tested in one case study – the development of a motorcycle tire dismounting tool. Product testing and interview survey was conducted to collect feedback from the users. All the three evaluation criteria (efficiency, comfortability, safety) scored a positive feedback from the users for the designed tool relative to the existing tool. The result indicates that an integration of UCD in the product development process had enhanced the establishment of user requirements in the product.